Gendering the Renaissance commonwealth - Becker, Anna 1978- (Cambridge University Press, 2020)
The civic and the domestic in Aristotelian thought -- Friendship, concord, and Machiavellian subversion -- Jean Bodin and the politics of the family -- Inclusions and exclusions -- Sovereign men and subjugated women. The invention of a tradition -- Conclusion : from wives to children, from husbands to fathers
Includes bibliographical references and index
Keywords: Geschlechterrolle; Renaissance; Geschlecht; Europa; Sex role / Europe / History; Renaissance / Europe